Ulasan Mekanisme Reduksi pada Proses Reduksi Langsung Konsentrat Pasir Besi atau Titanomagnetit - Imam Prasetyo; Wanidya Niimmallaili Hadining (Journal of Metallurgical Engineering and Processing Technology, 2022)
Research and developments that related to the utilization of titanomagnetite (TTM) or iron sand concentrate using direct reduction is more developed than blast furnace technology. The presence of titanium in the feed causes the blast furnace (BF) technology to be less appropriate. Mastery in the reduction behavior of iron sand concentrate or titanomagnetite is important as a basis for further technology development. The phase transformation of the iron oxide reduction process is generally known as follows: Fe₂O₃ → Fe₃O₄ → FeO → Fe. Meanwhile, based on the literature review that has been carried out, it is known that thermodynamically the requirement of CO/(CO+CO₂) partial pressure to reduce titanomagnetite concentrate is greater compared to the other iron oxides. The phase transformation that occur during the carbothermic reduction of iron sand or titanomagnetite concentrates have also been summarized in this review.